MANDATORY AUDIT OF FINANCIAL STATEMENTS: DOES AGRICULTURAL SECTOR DIFFER FROM OTHERS? - Kljajić, Maja; Mizdrakovic, Vule; Milojevic, Marko (Economics of Agriculture, 2021)
The main purpose of this paper is to determine if there are any differences when it comes to the type of opinion and content of audit reports between agricultural and other public companies (non-agricultural). Research sample consists of 398 public companies, and this number makes up about 70% of the total number of public companies listed on the Belgrade Stock Exchange. The sample was divided into two groups; one comprising companies from the agriculture, forestry and fishing sector (29); while the second group consists of public companies from other sectors (369). The research results indicate that companies in the first group received unqualified auditors opinions more often than second group companies. The similarity between the first and the second group is the dominant use of auditing services of domestic companies with an average share of 64.70% compared to the international and Big 4 auditing companies.